Patient Perception of Ideal Body Weight and the Effect of Body Mass Index - Rozhin Naghshizadian; Amir A. Rahnemai-Azar; Kruthi Kella; Michael M. Weber; Marius L. Calin; Shahida Bibi; Daniel T. Farkas (Journal of Obesity)
Objective. Despite much effort, obesity remains a significant public health problem. One of the main contributing factors is patients’ perception of their target ideal body weight. This study aimed to assess this perception. Methods. The study took place in an urban area, with the majority of participants in the study being Hispanic (65.7%) or African-American (28.0%). Patients presented to an outpatient clinic were surveyed regarding their ideal body weight and their ideal BMI calculated. Subsequently they were classified into different categories based on their actual measured BMI. Their responses for ideal BMI were compared. Results. In 254 surveys, mean measured BMI was 31.71 ± 8.01. Responses to ideal BMI had a range of 18.89–38.15 with a mean of 25.96 ± 3.25. Mean (±SD) ideal BMI for patients with a measured BMI of <18.5, 18.5–24.9, 25–29.9, and ≥30 was 20.14 ± 1.46, 23.11 ± 1.68, 25.69 ± 2.19, and 27.22 ± 3.31, respectively. These differences were highly significant (P<0.001, ANOVA). Conclusions. Most patients had an inflated sense of their target ideal body weight. Patients with higher measured BMI had higher target numbers for their ideal BMI. Better education of patients is critical for obesity prevention programs.